Deep Neck Lift: Defining Anatomical Problems and Choosing Appropriate Treatment Strategies - Marten, Timothy; Elyassnia, Dino (Facial Plastic Surgery, 2022)
A well-contoured neck is an artistic imperative to an attractive and appealing appearance. A good neckline conveys a sense of youth, health, fitness, confidence, and vitality and lends an appearance of decisiveness, sensuality, and beauty. Neck improvement is of high priority to almost every patient seeking facial improvement, and the results of “face lift” procedures are judged largely by the outcome obtained in the neck. If the neck is not sufficiently improved, our patients will often feel we have failed them. Despite the fact that it is a common practice, it is not enough to perform submental liposuction and tighten the skin and platysma in most patients as such an approach ignores a number of anatomical problems present in many patients seeking neck improvement including excess subplatysmal fat, large submandibular glands, and digastric muscle hypertrophy and malposition. Removing subcutaneous fat and tightening skin and platysma over these problems does not correct them, and the presence or absence of each must be looked for in order to create and apply an appropriate surgical plan. Success or failure in treating the neck lies in the diagnosis of underlying problems and the application of a logical surgical plan to correct them. Any surgeon capable of identifying the anatomic basis of patient problems and forming a sound plan for their correction will achieve excellent outcomes.
Keywords: neck lift; short scar neck lift; submandibular gland reduction; partial digastric myectomy; subplatysmal fat